Fundamental constants:a mystery of physics - Fritzsch Harald; Stodolsky Gregory , tr. (World Scientific, 2009)
The speed of light, the fine structure constant, and Newton's constant of gravity ? these are just three among the many physical constants that define our picture of the world. Where do they come from? Are they constant in time and across space? In this book, physicist and author Harald Fritzsch invites the reader to explore the mystery of the fundamental constants of physics in the company of Isaac Newton, Albert Einstein, and a modern-day physicist. The conversation that the three scientists are imagined to have provides an entertaining introduction to the constants and covers topics ranging from atomic, nuclear, and particle physics to astrophysics and cosmology.
Keywords: Physical constants